Construir para construir - Köncke, Florencia (Restauro Compás y Canto S.A., 2021)
This article elaborates a critical and alternative reasoning based on the concept of contemporary urban heritage. Delving into the origin of the term reflects its construction from specific geographical, historical and political contexts and, from there, awakens the appetite to reformulate the discourse by incorporating aspects inherent to our current cities. The notion of urban heritage includes visual, aesthetic and artistic aspects, but at the same time, it also encompasses symbolic and identity issues that are linked to the collective memory and the daily life of citizens. From the location and identification of cities in the process of development, where construction on vacant land is more frequent than demolition and subsequent construction, it becomes convenient to highlight that our crucial challenge does not yet refer to intervention but is in the construction. The construction of a characteristic identity and the collective commitment to forge our own heritage, a city that represents us and can reflect the interests, needs and concerns of those who live there. From the optimistic perspective that it is possible to make good architecture, it is imperative to recognize it under the shelter of urban heritage. That which describes a sensibility and a way of thinking, projecting and acting on what exists but also, and mainly, from what is yet to exist.